Substorm‐Related Near‐Earth Reconnection Surge: Combining Telescopic and Microscopic Views. Issue 12 (24th June 2019) - Sergeev, V. A.; Apatenkov, S. V.; Nakamura, R.; Baumjohann, W.; Khotyaintsev, Y. V.; Kauristie, K.; van de Kamp, M.; Burch, J. L.; Ergun, R. E.; Lindqvist, P.‐A.; Torbert, R.; Russell, C. T.; et al.
Abstract: A strong 11‐min‐long surge of the lobe reconnection was observed during a substorm on the tailward side of the near‐Earth neutral line. In the southern lobe near the reconnection separatrix the MMS spacecraft observed short‐duration earthward electron beams providing the local Hall current, tailward propagating Alfven wave (AW) bursts with Poynting flux up to 10 −4 W/m 2, and large‐amplitude E field spikes (e‐holes) and low hybrid waves. The reconnection surge was accompanied by substorm current wedge formation and fast poleward expansion of auroral bulge‐related westward electrojet in the conjugate ionosphere. During its meridional crossing above the expanding bulge the Metop‐2 spacecraft observed an intense energetic precipitation spike near the expected X line foot point and confirmed the dipolarized character of magnetic field lines inside of the bulge. Globally the observed average reconnection rate (< Ey > 3.3 mV/m) was sufficient to produce the magnetic flux increase in the bulge, associated with observed fast poleward expansion (about 6° latitude in 5 min). Plain Language Summary: Although magnetic reconnection in the magnetotail has been proposed to be the core process for the strong global magnetospheric reconfiguration and for huge particle acceleration during magnetospheric substorms, this association is mostly based on indirect evidence, because reconnection intermittently activates in different parts of the tail current sheet, and it is difficult to monitor its location and intensity variations based on direct spacecraft observations. On 28 July 2017 the MMS spacecraft succeeded in staying in the magnetotail near the active reconnection separatrix for a relatively long time during the surge of reconnection. At the same time the electric currents were enhanced and moved poleward in the magnetically conjugate part of the ionosphere, indicating configurational changes in the magnetotail. At the same minute the Metop‐2 spacecraft in low‐Earth orbit passed above this region and detected precipitating electrons of different energies as well as their distribution in the loss cone, which yielded conclusions about the strength of the equatorial magnetic field in the reconnected flux tubes. This unprecedented combination of conjugate observations allows us to confirm directly the important global consequences of an intense near‐Earth reconnection event, which have been suggested in the near‐Earth neutral line substorm scenario but could not be previously observed together in the same event. Key Points: MMS observed 11‐min‐long lobe reconnection surge near the separatrix during fast poleward electrojet expansion in the conjugate ionosphere Intense hard electron precipitation near the footpoint of the neutral line and dipolarized fieldlines in the interior of auroral bulge are confirmed Direct link and consistence of poleward auroral expansion and reconnection rates are demonstrated